Precise measurement of stable potassium isotope ratios using a single focusing collision cell multi-collector ICP-MS. Issue 4 (8th March 2016) - Li, Weiqiang; Beard, Brian L.; Li, Shilei
Abstract : High precision potassium isotope ratio measurements were made using a collision-cell equipped single focusing Multi-Collector Inductively Coupled Plasma Mass Spectrometer (MC-ICP-MS). Abstract : High precision potassium isotope ratio measurements were made using a collision-cell equipped single focusing Multi-Collector Inductively Coupled Plasma Mass Spectrometer (MC-ICP-MS). Interferences on 41 K from 40 ArH + were largely suppressed through collision with He gas atoms, and reaction with H2 or D2 gas molecules in the collision cell under optimum collision gas flow conditions. Using H2 or D2 as the collision gas, we distinguish charged argon–deuterium molecules (ArD + ) generated in the collision cell from argon hydride (ArH + ) generated in the plasma or in the interface region (referred to as "plasma-related AH + " hereafter), and demonstrate, for the first time, that both plasma-related and collision cell-generated ArH + are important sources of ArH + that interfere with 41 K + in collision-cell ICP-MS instruments that use H2 as a collision gas. The use of D2 instead of H2 as a reactive gas in the collision cell resulted in better overall performance in K isotope ratio measurements. By combining these mass spectrometry methods with chemical purification of K by ion exchange chromatography, we achieved an internal precision of <±0.07‰ (2 standard error) and an external reproducibility of <±0.21‰ (2 standard deviation, or 95% confidence) in the 41 K/ 39 K ratio measurement for geological and biological samples. With the improved precision, it is possible to distinguish a ∼1.3‰ variation in K isotope compositions ( 41 K/ 39 K ratios) among seawater, igneous rocks, and biological samples. The K isotope system is likely to be beneficial in providing a better understanding of potassium cycling during continental weathering and the uptake of nutrients by plants.